THE IMPORTANCE OF NOBLE CHARACTERS FOR KNOWLEDGE SEEKERS - Rasman Bin Saridin (Proceeding International Seminar of Islamic Studies, 2021)
From the above outline, it can be concluded that the end-purpose of good characters for knowledge seeker is to give birth to civilized scholars, as was the idea of tadib of Prof. Al-Attas, namely civilized humans who apply manner in every aspect: having good characters towards God, oneself, the social environment, human relationship, language, nature, and knowledge. Having good characters towards knowledge will affect other objects. Intellectuals who have good characters towards knowledge will recognize and admit that people with knowledge have a higher and nobler position and the compulsary knowledge and law must be mastered first before other knowledge. Knowledge seekers with good characters can be expected to defend the law because there are so many deviations of knowledge that appear one after another, sometimes it is impossible to defend them except by the knowledge seekers. They are also generous in responding to the differences of opinion among scholars. Keywords: Noble Characters, Knowledge, Knowledge Seekers